CONFLICT ON THE PROTECTION OF HUMAN RIGHTS RELATED TO TRADEMARK RIGHTS AND PUBLIC HEALTH RIGHTS: PROHIBITION OF DISPLAY OF CIGARETTE PACKAGES AT POINT-OF-SALE BASED ON INDONESIA'S POSITIVE LAW - Tamara Putri Berliani; Muhamad Amirulloh; Eddy Damian (Jurnal Poros Hukum Padjadjaran, 2022)
In attempt to reduce tobacco consumption and implement preventive measures through regulations such as the prohibition of displaying cigarette packs at points of sale regulated by the WHO FCTC, a dilemma arises regarding the protection of the intellectual property rights of trade owners, with public health. Based on this background, this study aims to examine two objectives. First, regarding what legal theory may be used as a legal basis for Trademark Rights owners against the prohibition of displaying cigarette packs at points of sale and second, regarding whether the implementation of Law Number 20 of 2016 concerning Trademarks and Geographical Indications violates the WHO Framework Convention on Tobacco Control 2003 regarding the prohibition of displaying cigarette packs in points of sale. This study uses an adjusted approach method in this writing, namely through normative juridical and qualitative juridical approaches.